4 Examining x, y, and z vibration patterns of commercial pig transport trailers from the farm to the abattoir. (30th November 2020) - Gonzalez, John M; Davis, Ben; Morris, Benjamin; Brokesh, Edwin; Flippo, Daniel; Houser, Terry; Najar-Villarreal, Francisco; Turner, Kari; Williams, Jamison
Abstract: The objective of this study was to measure and examine 3-axis acceleration data from 6 locations within commercial transport trailers shipping market pigs. Over winter months (December through February) of 2018 to 2019 and 2019 to 2020, 16 pot-belly and 14 straight-deck trailer loads of market pigs were measured from 2 producers located in Kansas and North Carolina, respectively. Six accelerometers were placed in protective cases and affixed to the underside of the floor in the approximate center of the front compartment, middle of the trailer, and back compartment of the top and bottom decks. Data were post-processed to calculate power spectral density (PSD) functions and corresponding root mean square (RMS) accelerations. The PSDs lend insight into the vibrational frequency content of the trailers, while the RMS values indicate the severity of the vibration over the duration of each trip. With the exception of the lower aft portion of the trailer where levels are significantly higher, RMS values were consistent across trips and largely similar between sensor location and axis. Accelerations ranged between 0.06 and 0.18 g and varied in time, indicating data were non-stationarity. The PSD results reveal a largely broadband frequency response of the loaded trailers between 0 and 50 Hz, especially for sensors on the lower deck. Preliminary analysis of the data indicates the severity of vibrations experienced by pigs during transport would be considered uncomfortable by humans.